2022
DOI: 10.1002/ece3.8572
|View full text |Cite
|
Sign up to set email alerts
|

Altitude‐mediated soil properties, not geography or climatic distance, explain the distribution of a tropical endemic herb

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
(77 reference statements)
1
1
0
Order By: Relevance
“…The absence of decreasing population growth rate toward range periphery is not surprising given the greater relative importance of survival‐growth to population fitness than fertility which is a typical trait of long‐lived species. Consistent with our findings on population growth rates, our previous study on the same system showed no significant variation in population abundance between range center and periphery (Moutouama & Gaoue, 2022a). These convergent results of two different metrics (e.g., population abundance and population growth rate) must not be interpreted as if population abundance could be used as a surrogate measure of population growth rate.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The absence of decreasing population growth rate toward range periphery is not surprising given the greater relative importance of survival‐growth to population fitness than fertility which is a typical trait of long‐lived species. Consistent with our findings on population growth rates, our previous study on the same system showed no significant variation in population abundance between range center and periphery (Moutouama & Gaoue, 2022a). These convergent results of two different metrics (e.g., population abundance and population growth rate) must not be interpreted as if population abundance could be used as a surrogate measure of population growth rate.…”
Section: Discussionsupporting
confidence: 93%
“…This distribution pattern is often explained by the expectation that the most favorable ecological conditions (biotic and abiotic) exist at the center of distribution. However, the geographic center of distribution does not necessarily coincide with species' optimal climatic conditions (Moutouama & Gaoue, 2022a). Therefore, species are not always expected to be most abundant at the center of their range, and this limits the generalization of the center‐periphery hypothesis (Dallas et al, 2017; Pironon et al, 2017).…”
Section: Introductionmentioning
confidence: 99%